2021
DOI: 10.1002/mp.15067
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning and 4D robust evaluation strategy for proton therapy of lung tumors with large motion amplitude

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Both studies showed that small-spot IMPT decreases doses to nearby normal tissues compared to VMAT as well as achieves clinically acceptable plan robustness. Taasti et al investigated ITV-based minimax optimized plans for lung tumours with motion amplitudes up to 26 mm [63]. For evaluation, three different robust evaluation approaches were employed, although the investigators did not account for the interplay effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies showed that small-spot IMPT decreases doses to nearby normal tissues compared to VMAT as well as achieves clinically acceptable plan robustness. Taasti et al investigated ITV-based minimax optimized plans for lung tumours with motion amplitudes up to 26 mm [63]. For evaluation, three different robust evaluation approaches were employed, although the investigators did not account for the interplay effect.…”
Section: Resultsmentioning
confidence: 99%
“…Taasti 2021 [63] The ITV-based planning method was found to provide plans with adequate tumour coverage and no OAR overdosage even for large tumor movement.…”
Section: Publication Conclusion 3d Optimization Conclusion 4d Mib Opt...mentioning
confidence: 99%
“…For the lung and lymphoma patients, the doses were computed on an average CT (CTavg) based on a 4DCT scan, for both the pCT and the reCTs. The targets and OARs were delineated on the 50% expiration phase (CT50ex) and rigidly copied to the CTavg [3] . In the automated workflow, the target contours were therefore also deformably propagated from the pCT50ex to the reCT50ex and then rigidly copied to the reCTavg.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore wanted to assess if this step could be replaced by deformable image registration (DIR) between the treatment planning-CT (pCT) and the following reCTs. DIR has previously been shown to provide good results for reCTs of head-and-neck (HN) patients [2] and 4DCTs for lung patients [3] . In this study, we included a mixed cohort of patients (brain, HN, breast, lung and lymphoma) treated with proton therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Plan robustness shows to what degree anatomical change and setup uncertainty would affect the daily delivered dose in the patient's body [17][18][19] ; thus robustness must be included in our consideration. Proton pencil-beam plans are usually created to be robust on proton range and setup uncertainties and, in some situations, anatomical change.…”
Section: Introductionmentioning
confidence: 99%